The Influence of Religion in Intra-School Student Organizations on the Character Building of Students at Proklamasi Vocational High School in Karawang - Aisyah, Siti; Kejora, Muhamad Taufik Bintang; Akil, Akil (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The character and morals of students in Indonesia today are very worrying. The declining character and morale of students is also felt by the Proklamasi Vocational School, Karawang Regency, West Java Province. This is a problem that needs to be resolved and I think that the Religious Sector in the Intra-School Student Organization (OSIS) can be a solution to solve the problem of adolescent delinquency and the declining spiritual attitudes of students at SMK ProkIamasi Karawang. This study aims to find out what are the effects of the Religious Sector in Intra-School Student Organizations (OSIS) on the Spiritual Attitudes of Students at SMK ProkIamasi Karawang. Based on research on the influence of the field of Religion in Student Organizations on the Character Building of Vocational High School Students Proklamasi is to create an educational institution environment that supports and can become a laboratory for the delivery of religious education, religious education is not only delivered formally in the implementation of the delivery of religious teaching materials, but can also be carried out in Outside the learning process, creating religious situations and conditions, providing opportunities for students to express themselves, fostering talents, interests, and creativity in religious education in skills and arts, by organizing various kinds of competitions such as intelligence to train and develop courage, speed and accuracy. day to convey knowledge and practice the religious education material obtained